Interface entre arquitetura bioclimática e decisões projetuais - Rangel, Pollyana de Faria (2008)
This research has as its object study focus bioclimatic in architecture and its conection with projects decisions, on what regards to environmental comfort for single-family dwelling. From the analysis of five architectural projects inserted in Natal/RN, warm-moist weather, this research gather informations regarding architectural features guided by shape and space arrengement, which embody important elements for the project design development. Computer simulations assisted as foundation to verify the efficiency grade for these projects strategies from shading analysis. Related strategies for the demands of natural ventilation circulation and thermal mass for refrigeration were analysed as well. Results show that there is an hierarchizing of priorities for the decisions made when it comes to shape and space disposition variables, as well as the way these variables will consider the bioclimatic demands. The analysis, even, show that there is no single way to respond to specific bioclimatic demands, as it points out the value of examination of the projectual solutions throughtout the conception process, in order to achieve an efficient project performance for the envimonment comfort